Innovationsfähigkeit im demografischen Wandel - Entwicklung und Validierung des Assessment-Tools NovaDemo zur Erfassung der Innovationsfähigkeit von Einzelpersonen und Arbeitsgruppen - Waßmann, Stefan (Karlsruher Forschungsberichte zur Arbeitswissenschaft und Betriebsorganisation / Institut für Arbeitswissenschaft und Betriebsorganisation (ifab), Karlsruher Institut für Technologie, 2014)
This book describes the development and validation of the Assessment-Tool NovaDemo based on relevant theories as well as qualitative pre-studies. This Assessment-Tool is a novel multi methodological Instrument for the diagnosis of the innovative ability of age-heterogeneous work groups.